PENGARUH BREASTFEEDING SELF-EFFICACY TERHADAP MOTIVASI IBU DALAM MENYUSUI TAHUN 2023 - Khoiriah, Restu (Politeknik Tiara Bunda, 2024)
Background : Exclusive breastfeeding is a condition where the baby is fed enough breast milk without any additional milk in the first six months. Exclusive breastfeeding plays an important role in maintaining the health and continuity of life and body immunity of babies. There are many factors that influence exclusive breastfeeding, one of which is breastfeeding self-efficacy. Breastfeeding self- efficacy is a belief in a mother to breastfeed her baby. Breastfeeding self-efficacy is a psychometric factor that has a positive influence on increasing exclusive breastfeeding. Objective :The aim of this research is to determine the relationship between breastfeeding self-efficacy and exclusive breastfeeding for breastfeeding mothers Method :Type of quantitative research with a cross sectional approach. The sample used isbreastfeeding mothers who have babies aged 6-24 monthsin the Bandarharjo Health Center area, Semarang. The technique used was purposive sampling of 100 respondents. The correlation test used in this research is the spearmen rank test Results :The results of research conducted using the Spearman correlation test showed a p-value of 0.00 (<0.05), indicating that there was a relationship between breastfeeding self-efficacy and exclusive breastfeeding in Kuningan Bandarharjo Village, Semarang with a correlation coefficient of 0.482, indicating that the relationship was moderate. positive correlation direction. Conclusion:There is a relationship between breastfeeding self-efficacy and exclusive breastfeeding for breastfeeding mothers in the Bandarharjo Health Center Working Area, Semarang.